The effect of a core antigen vaccine on health and performance of cattle diagnosed with bovine respiratory disease - Gerald L. Stokka; Robert T. Brandt Jr.; K.K. Kreikemeier; T. Milton (Kansas Agricultural Experiment Station Research Reports, 1995)
When studied in receiving trials at three locations, health or performance of calves receiving a core antigen vaccine was not improved.
Keywords: Cattlemen& #x27; s Day; 1995; Kansas Agricultural Experiment Station contribution; no. 95-357-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 727; Beef; Core antigen; Vaccine; Health; Performance